Policy recommendations for enhancing human resource management and bank competitiveness: Evidence from commercial banks in Vietnam - Nga, Lu Phi; Tam, Phan Thanh (International Journal of Innovative Research and Scientific Studies, 2025)
Human resource management plays a vital role in banking activities and is essential for ensuring sustainable development and improving the competitiveness of commercial banks. Currently, the issue of human resource management in banking activities still has certain limitations and difficulties that have significantly affected competitiveness. Therefore, this study aims to determine the influencing factors and their degree of influence on the human resource management of commercial banks in Vietnam. Based on these factors and their impact on human resource management, the authors proposed solutions to improve human resource management to enhance banks’ competitiveness. This study uses a combination of qualitative and quantitative research methods. The study applied qualitative methods through expert methods and in-depth interview methods from 10 bank leaders, quantified from primary data collected by the survey authors through 350 questionnaires from 350 employees working in 10 commercial banks in 10 provinces in Vietnam. SPSS 20.0 and Amos software were used to quantify the degree of influence of the factors. The study identified six factors: leader support, training and developing human resources, work environment, employee benefits and regimes, incentive policies, and control and evaluation. Finally, the application helps banks ensure sufficient human resource management and appropriate bank competitiveness.